A personalized approach to long QT syndrome. (January 2019) - Etheridge, Susan Payne; Asaki, Sarah Yukiko; Niu, Mary Chun-I
Abstract : Purpose of review: Our purpose is to provide an update on the new clinical and genetic aspects of long QT syndrome (LQTS). LQTS is the most common channelopathy and a cause of syncope and sudden death in the young. Although there are 17 types of LQTS, most patients have types 1 or 2 which are due to mutations in KCNQ1 and KCNH2 (encoding for the cardiac potassium channels), and type 3 which is due to a mutation in SCN5A (encoding for the sodium channel). LQTS is characterized by incomplete penetrance and variable expressivity. Significant data exist concerning the common types of LQTS and include mutational location, biophysical function, gene-specific triggers, and disease modifiers that are known and help characterize the disease. Recent findings: Recent studies support the use of β-blockers in LQTS. Nadolol and propranolol are superior likely because of their sodium channel blocking effects. There are recent data supporting the use of β-blockers in LQTS type 3 in which their use was once discouraged. There are increasing data that left cardiac sympathetic denervation is effective in LQTS and should be considered before an implantable cardioverter defibrillator is implanted. Summary: LQTS is a model for effective collaboration between clinicians and basic scientists and between cardiologists and geneticists. Recent advances in the derivation of induced pluripotent stem cells from LQTS patients and creation of genetically engineered human models using clusters of regularly interspaced palindromic repeats (CRISPR/Cas9) will advance translational arrhythmia research and move us toward the goal of personalized medicine. Abstract : Supplemental Digital Content is available in the text